Itinerant curriculum theory: People's theory against the field's epistemicidal ethos (Praxis Educativa, 2026)
The field of curriculum studies suffers from a glaring theoretical impasse. Much of this impasse has been rightly attributed to the triumphalism of the neoliberal wave that has massacred the educational hemisphere with policies and practices that reduce pedagogy to an instrumentalist praxis directly associated with the thirsty desires and needs of the market. However, another substantive part of this impasse – and not much explored in our scholarly affairs – relatesto the apparent breakdown of many critical and post-critical approaches. The combination of these two axes – completely antagonistic – has contributed to the consolidation of the epistemicidal nature of the curriculum. At the core of this article is a clarion call for all the scholars in the field to counter such an impasse, deterritorializing their approaches and commit to an itinerant position to address the world's endlessly different and diverse epistemological traditions, disestablishing the eugenic nature of our field – its theory and development. The article also explores significant drawbacks faced by counter-hegemonic impulses in our field. In doing so, this article unveils the challenges of building a hegemonic critical pedagogical platform. It develops a laudatory eulogy for a collective engagement with an itinerant curriculum theory (ICT) as a just people's theory towards social and cognitive justice.
Keywords: curriculum epistemicida